Analysis of Differences in Improvement of Mathematical Problem Solving Ability of The Students at Upper Secondary School 3 Sidikalang Based on Contextual Learning Model And Direct Learning Models - Aritonang, Abden Rahim; Minarni, Ani; Rajagukguk, Wamington (Advances in Social Sciences Research Journal, 2018)
This research aims to analyze differences in the improvement of students' mathematical problem-solving ability (MPSA) through contextual learning model and direct learning model. Type of research is a quasi-experimental study. The research population was all students of upper secondary school (USS) at Sidikalang which consisted of nine classes by taking classes IX-4 and IX-5 as the sample. In this research students is categorized to master MPSA if they do MPSA test, they understand the problem, choosing a problem solving strategy, executing the strategy, and concluding the solution in line with the initial problem.Problems are designed contextually. Based on the results of this study it was found that there were differences in the improvement of MPSA between students taught through contextual learning model and through direct learning model and the students MPSA are categorized good. MPSA N-Gain of the taught through contextual learning models is higher than students taught through direct learning models.